IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH DENGAN INVESTASI TERHADAP KINERJA PEMERINTAH DALAM TINJAUAN ISLAM (STUDI KASUS DESA ULUMAHUAM) - Sutarno, Yungki; Harmain, Hendra; Wahyuni, Arnida (Jurnal Ilmiah Ekonomi Islam, 2023)
In this case it refers to the village government in an effort to implement SAP by investing in government performance. The investment made greatly influences the image of the community's environmental assessment of the performance of the village government, which then becomes a benchmark for considering the achievement of this leadership. This study aims to find out how the implementation is carried out by the Ulumahuam Village Government, because there are some uniqueness or differences that occur in the Village Government in general where the hypothesis includes the level of concern, wisdom, creativity and innovation possessed by the Ulumahuam Village Government. This research methodology is quantitative with a qualitative descriptive approach, where the focus of this research is to explore the specific problems of research subjects from all aspects of personality related to the object of research, this research is also often called casuistic research. The results showed that the significance value (0.817) > 0.05 means that there is no effect of the application of government accounting standards by investment on government performance or in other words it can be concluded that the application of SAP through investment is not in accordance with government performance.